2014
DOI: 10.1590/s1983-40632014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Genótipos de trigo em diferentes densidades de semeadura

Abstract: A capacidade de perfilhamento em trigo define os componentes de rendimento e a produtividade, sendo afetada pela densidade de semeadura. Objetivou-se, neste estudo, avaliar genótipos de trigo cultivados em diferentes densidades de semeadura, em Londrina e Ponta Grossa (PR), nos anos de 2009 e 2010. Utilizou-se o delineamento experimental em blocos ao acaso, em esquema fatorial, com quatro repetições. Foram avaliados os aspectos agronômicos de três genótipos de trigo (PF 014384, BRS Tangará e BRS Pardela), nas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
2
16
0
5
Order By: Relevance
“…This author confers this reduction to the existing competition due to the increase in seed sowing density. However, Tavares et al (2014) found no significant difference for grain mass at densities of 150 to 450 m² plants.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…This author confers this reduction to the existing competition due to the increase in seed sowing density. However, Tavares et al (2014) found no significant difference for grain mass at densities of 150 to 450 m² plants.…”
Section: Resultsmentioning
confidence: 66%
“…For the variable hectolitric, Tavares et al (2014) , concluded that the yield varies according to the genotype used, and some cultivars have a lower capacity of compensation in relation to others, that is, each cultivar has a different performance when subjected to random plant reduction.…”
Section: Resultsmentioning
confidence: 99%
“…However, under favorable weather conditions, the use of high rates of nitrogen is not always the most appropriate strategy. The increase of grain yield can be achieved by improvements of the utilization efficiency of the fertilizer by the plant (Tavares et al, 2014).…”
Section: Days After Emergence (Dae)mentioning
confidence: 99%
“…Os genótipos são afetados de forma distinta pela densidade de semeadura (OZTURK et al, 2006) pois apresentam diferenças na capacidade de perfilhamento (TAVARES et al, 2014). Cultivares com maior potencial de perfilhamento são capazes de manter elevada a produtividade de sementes, mesmo quando cultivadas em baixas densidades, diferentemente de cultivares com baixo perfilhamento, que dependem de uma maior densidade de semeadura, já que são menos eficientes em compensar o menor número de espigas por unidade de área (VALÉRIO et al, 2009).…”
Section: Introductionunclassified